Proposals for revisions of the classification of lung cancers with multiple pulmonary sites: the radiologist’s, thoracic surgeon’s and oncologist’s point of view - Rizzo, Stefania; Petrella, Francesco; Passaro, Antonio; Marinis, Filippo de; Bellomi, Massimo (Journal of Thoracic Disease, 2016)
The primary goal of tumor, node and metastasis (TNM) classification is to provide a nomenclature for tumor extent that creates homogeneous cohorts of tumors.